Design and fabrication of rice milling machine for paddy farmers at Samarahan, Sarawak - Mohd Hazrul Azli, Abu Bakar (Universiti Malaysia Sarawak (UNIMAS), 2010)
The rice milling machine has been used by the farmers all over the world and is also practiced by the paddy farmers in Samarahan, Sarawak. The rice milling machine is an economical mechanism to turn a paddy into rice. Thus, the purpose of this study is to improve, design, fabricate and test the performance of a proposed rice milling machine against the existing rice milling machine in Samarahan. An active rice milling machine was designed, fabricate and tested to mill the paddy. Two fans with 12V were installed to the proposed machine as the winnowing system. A sieve system was also installed to increase the machine performance. Four major tests were performed. The first test evaluated the importance and effectiveness of the paddy to be dried before mille and it was discovered that by drying the paddy before milling can increase the successful rate of milled rice up to 46%. The second test shows the relationship of the gap distance between the blade and the ribbed cylinder to the paddy milling efficiency, for these proposed rice milling machine, the desired blade distance for Hill Paddy is 4 millimetre gap between the blade and the rotating ribbed cylinder. Data from the third test supported that the proposed winnowing system was successfully operated with an acceptable speed rate of minimum 3 m/s and cutting the daily winnowing cost about RM3.91. Result from the fourth test showed that the sieving was functioning properly where it’s successfully filter the entire husk that still remain after winnowing.